PENETAPAN KADAR ASAM LEMAK BEBAS PADA BERBAGAI MINYAK GORENG SETELAH DAN SEBELUM PENGGORENGAN DENGAN METODE TITRASI ALKALIMETRI - Iswandi Iswandi; Eva Widhia Saprini Sipa; Endang Sri Rejeki (LPPM Akafarma Sunan Giri Ponorogo, 2023)
Food is needed to develop individual actual knowledge so that food must be of good quality and nutritious. One of them is cooking oil which is used to fry food. Heating when frying causes an increase in free fatty acids. This study aims to determine the levels of free fatty acids in various cooking oils after and before frying with a variation of one time to meet government quality raw material standards. Free fatty acid content test in bulk cooking oil of palm oil, sunflower seed oil, soybean oil after and before frying using the alkalimetric titration method. The One Way Anova test was carried out to see if there was a difference in the increase in free fatty acid levels of the three cooking oils, and continued with the Tukey test. The government quality standard for palm oil and sunflower seed oil is a maximum of 0.30%. The results showed that palm cooking oil before frying was 0.44% and after one time frying was 0.61%, sunflower seed cooking oil before frying was 0.32% and after one frying time was 0.76%. Soybean oil at the time of research before frying 0.31% and after one frying 0.59%, this shows that it meets government quality standards with a maximum of 2.00%.